Labour Confronts the Millennium = Le Travail au prochain millénaire - Palmer, Bryan D. (Labour / Le Travail, 2000)
Introduces the special volume that marks the millennium, including the painting, "Labouring the Millennium," by Ellison Robertson, commissioned by Labour/Le Travail and reproduced on the cover.